Analisis Pengaruh Penghargaan Finansial, Pertimbangan Pasar Kerja, Lingkungan Keluarga Dan Fleksibilitas Kerja Terhadap Minat Menjadi Akuntan Publik (Studi Empiris Mahasiswa Akuntansi Perguruan Tinggi Negeri Di Kota Padang) - May Neni Elviadmi; Desi Handayani; Dita Maretha Rissi (Politeknik Negeri Padang, 2022)
This study aims to determine the effect of financial rewards, labor market considerations, family environment and work flexibility on interest in becoming a public accountant. This research is a quantitative research. The method of data collection was using a questionnaire instrument which was distributed online via google form . Distributed to accounting students of state universities in Padang City who have met the criteria. The sample used was 204 people using the proportional stratified random sampling method . Analysis of the data used is multiple linear regression analysis using SPSS version 25. Based on the results of data processing, it can be concluded that financial rewards, labor market considerations, family environment and work flexibility have a positive and significant effect on interest in becoming a public accountant. Keywords: Interests, Public Accountants, Financial Awards, Labor Market Considerations, Family Environment and Work Flexibility